PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN DEEP LEARNING BERBASIS AKTIVITAS BERMAKNA, MENYENANGKAN, DAN REFLEKTIF PADA SISWA KELAS II SD NEGERI 1 MUTIHAN - Suwartini , Sri; Azizah, Afidlotul; Karim Adhani , Alfath; Rohmaniah , Alfiatur; Suciati, Andita; Ermawati , Defi; Wisnhu Ardanie , Della (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary school plays an important role in developing students' logical and systematic thinking skills. However, initial observations in Grade II at SD Negeri 1 Mutihan showed conventional, teacher-centered learning, causing difficulties with whole-number concepts and simple data presentation, with a pre-cycle average score of 66.78 and 47.8% classical completeness. This study aimed to describe the implementation of a deep learning approach based on meaningful, joyful, and mindful learning activities and to improve the mathematics learning outcomes of Grade II students at SD Negeri 1 Mutihan. The study used the Kemmis and McTaggart Classroom Action Research model across three cycles in April 2026, involving 23 second-grade students. Data were collected through formative and summative tests, questionnaires, and documentation, then analyzed descriptively and supported by Normalized Gain (N-Gain) analysis. Results showed the average score rose from 66.78 (pre-cycle) to 82.17 (Cycle I, 82.6% completeness), 84.04 (Cycle II, 87.0%), and 86.65 (Cycle III, 100%). N-Gain analysis showed moderate improvement across all indicators: reading-writing numbers and place value (0.46), comparing numbers (0.52), and presenting data (0.60), with an overall N-Gain of 0.60 (moderate). The deep learning approach based on meaningful, joyful, and mindful activities was thus effective in improving students' mathematics learning outcomes.